Estudo do comportamento de argamassas com agregado reciclado misto de RCD produzidas com o método de mistura da NBR 16541 - Souza, Juliane Santos (2020)
The use of recycled aggregate (RA) from construction and demolition waste (CDW) for the production of mortars has been studied in recent years. However, the mixing sequence is the least aspect considered for the production of recycled mortars. In this context, the present study aims to verify the behavior of mortars with CDW RA produced according to the method of NBR 16541 (ABNT, 2016). The levels of RA applied in partial replacement to the natural aggregate were 15 and 30 %. For this work, the consistency index test served as a parameter for evaluating the behavior of recycled mortars in terms of the mixing method used. In the fresh state, the properties of water retention, bulk density and incorporated air content were analyzed. In the hardened state, the compressive strength and flexural tensile strength, absorption by immersion, void index, and the specific gravity, absorption by capillarity, permeability and drying shrinkage were verified. The results indicate that the higher the percentage of RA, the drier the appearance of the mixtures, requiring a greater consumption of water to obtain a spread similar to the reference mixture. Besides that, changes in properties were observed in the fresh and hardened state, however, the results indicate that it is possible to use up to 30% of RA without the application of these mortars being impracticable, as long as they are produced according to the procedures described in this study.